Faktor yang Berhubungan dengan Efektivitas Pelayanan Ambulans Motor - Endri, Gunawan; Hadi, Muhammad; Naryati, Naryati (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT                                        Background A motorbike ambulance is a vehicle used to fulfil the response time of emergency victims. After the patient is stabilised, the patient will be taken by ambulance transport or emergency ambulance to the nearest health care facility. The purpose of this study was to analyse the factors associated with the effectiveness of motor ambulance services. used cross sectional measurement of independent and dependent variables assessed simultaneously at the same time. There is a significant relationship between officer readiness with a p-value of 0.000 <0.05, training factors with a P Value = 0.025 or <0.05, dispatch communication factors with a P Value = 0.000 or <0.05, unit readiness factor and medical equipment with a P Value = 0.000 or < 0.05, geographical factors with a P Value = 0.000 or < 0.05, and experience with a p-value of 0.000 < 0.05 with the effectiveness of motor ambulance services with a p-value of 0.000 (p-value ≤ 0.05). The factors that most influence the effectiveness of motor ambulance services are officer readiness (7.129), dispatch communication (21.079), and unit and medical equipment readiness (7.433). Keywords: Effectiveness, Service, Motorbike Ambulance ABSTRAK Ambulans motor merupakan kendaraan yang digunakan untuk memenuhi waktu respon penanganan korban gawat darurat. Setelah pasien stabil, maka pasien akan dibawa menggunakan ambulans transport atau ambulans gawat darurat menuju fasilitas pelayanan kesehatan terdekat. Ini untuk menganalisis faktor yang berhubungan dengan efektivitas pelayanan ambulans motor. Desain penelitian menggunakan cross sectional pengukuran variabel independen dan dependen dinilai secara simultan pada waktu yang sama.Terdapat hubungan yang bermakna antara kesiapan petugas dengan nilai p-value 0,000< 0,05, faktor pelatihan dengan dilai P Value = 0,025 atau < 0,05, faktor komunikasi dispatch dengan nilai P Value = 0,000 atau < 0,05, faktor kesiapan unit dan alkes dengan dilai P Value = 0,000 atau < 0,05, faktor geografis dengan nilai P Value = 0,000 atau < 0,05, dan pengalaman dengan nilai p-value 0,000< 0,05 dengan efektivitas pelayanan ambulans motor dengan p-value 0,000 (p-value ≤ 0,05). Faktor yang paling mempengaruhi efektivitas pelayanan ambulans motor kesiapan petugas (7,129), komunikasi dispatch (21,079), dan kesiapan unit dan alkes (7,433). Kata Kunci: Efektivitas, Pelayanan, Ambulans Motor